A Quality Control Study on Alliance Global, Inc. - Lugue, Tess Marichie; Macalinao, Laura Karen Grace P.; So, Sheryl Lyn M. (Diliman, Quezon City College of Engineering, 2001)
Alliance Global, Incorporated (formerly Anglo Watson's Philippines, Incorporated) started its glass manufacturing operations in October 1993. In 1995, a year round operation in Canlubang, Laguna was initiated and since then, Alliance Global, Inc. (AGI) has grown into the flint glass company that it is now. It was very ideal sight for the study since quality control is very important in this type of manufacturing system. Initially, a Failure Mode Effect and Criticality Analysis (FMECA) was conducted for the company. To prioritize possible failures, a Pareto Chart was constructed and it was found out that the top 3 failures (defects in the company's case) include off-weight bottles, finish checks and fractured bases. After this, a Cause and Effect Diagram showed that the shearing mechanism and raw material composition causes off-weight bottles. Finish checks are caused by the immediate subjection of the bottles into the annealing lehr. Lastly, fractured bottoms are caused by the pressure on the gob as it is dropped. All three are possibly caused by the cavity used. Control charts were made for the three problems and it was found out that the shearing and the cooling processes were both initially out of control. Assignable causes were found and the new control limits for each were recomputed and no outliers were found. Process Capability analysis was done and it was found that the shearing process has a Cp = 1.96, Cpk=-0.283, Cpl=-0.0144 and P=51.02%, the cooling process (finish checks) has a Cp=.3204, Cpk=-4405, P=89.73% and the cooling process (fractured bottom) has Cp=.8252, Cpk=.2511 and P=38.59%. Quality cost was computed for each problem. For off weight, the total quality cost was P4688.67/day, for finish checks P2009.69/day and for fractured bottom P1418.47/day. Recommendations regarding off-weight bottles include purchase of new computerized glass forming machine which was compared with the old machine using the Equivalent Worth Method and use of tighter control limits. For finish check, it was recommended that they change cavities every 12 hours after analyzing its MTBF (Mean Time Before Failure). The conveyor should be lengthen by 5 meters giving them an additional savings of P65,301.50/year (for both finish checks and fractured bottom.) A new design for the distributor nozzle was also recommended.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Alliance Global Incorporated; Glass industry; Quality control